Assessment of typical values for establishing institutional DRL of adult whole-body fluorine-18 fluorodeoxyglucose (FDG) PET/CT scans in Malaysia Cancer Centre - Murat, H.; Kechik, M. M. A.; Said, M. A.; Saufi, S. I.; Zaid, M. H. M.; Karim, M. K. A. (Elsevier, 2025)
Since 1996, Diagnostic Reference Level (DRL) has been introduced as an essential benchmark for optimizing patient radiation protection in a medical setting. DRLs have been acknowledged and reported by several institutions even become part of authority to monitor the use of radiation in medical, including diagnostic nuclear medicine imaging. Hence, this study aimed to establish DRL typical values for adult whole-body Fluorine-18 Fluorodeoxyglucose (WB FDG) PET/CT scan and to compare these values with other references. We retrospectively analyzed 831 adult patients (mean weight, 69.08 ± 5.84 kg and BMI, 26.01 ± 3.19 kg/m2) of their administered activity (A), administered activity concentration (CA), volume weighted computed tomography dose index (CTDIvol), dose length product (DLP) and effective dose (EPET/CT). Descriptive statistical methods were used to determine the median as the typical values and assess their alignment with other reference levels. The results showed that the median A was 296.37 MBq, while the median CA was 4.31 MBq/kg. For CT, the median CTDIvol was 7.77 mGy, and the median DLP was 818.34 mGy cm with the mean CT effective dose, ECT contributing nearly 70 % of total EPET/CT. Additionally, BMI was found to significantly affect radiation dose (p < 0.05) particularly in the CT, where dose increased with higher BMI. Our findings indicate that patient radiation protection for adult WB FDG PET/CT scans at our cancer center generally meet international standards. However, the observed dose variability suggests a need for further optimization to ensure more consistent application of DRL process.